Effect of Glucose on Attachment and Proliferation of Human Gingival Fibroblasts on Zirconia and Titanium Surfaces: Glucose Effect on Cellular Behavior on Zirconia and Titanium - Keshavarz, Sadaf; Torshabi, Maryam; Zamanian, Amirhosein; Rezaei Esfahrood, Zeinab (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Background and objectives: Diabetes-induced delayed wound healing compromises dental implant success by impairing junctional epithelium formation. This study evaluated the effects of various glucose concentrations on human gingival fibroblast (HGF) proliferation and attachment to titanium and zirconia surfaces. Materials and methods: Titanium and zirconia discs (2 × 10 mm) were prepared. HGFs were cultured on the discs or empty polystyrene plates (control) at glucose concentrations of 5.5, 11, 22, and 33 mM. Cell viability/proliferation and attachment were evaluated after 24 and 72 h using MTT assay and scanning electron microscopy (SEM). Statistical analysis was performed using one-way ANOVA and post-hoc Tukey test (P < 0.05). Results: Glucose concentration did not significantly affect cell viability/attachment within each material group. However, HGFs proliferated significantly between 24 and 72 h at 5.5 and 11 mM glucose on titanium, and at all concentrations on zirconia. Cell viability was similar between titanium and zirconia at all concentrations except 11 mM, where zirconia performed better. At 72 h, zirconia showed significantly higher cell attachment than titanium at high glucose concentrations (22 and 33 mM). Conclusion: Glucose did not affect initial cell attachment, but prolonged incubation (72 h) reduced cell-surface affinity on both metals compared to polystyrene. Nevertheless, zirconia promoted better HGF proliferation and attachment than titanium under high glucose conditions, suggesting zirconia as a preferable abutment material for diabetic patients.